Water-based thermal insulation coating and preparation method thereof
By preparing a water-based thermal insulation coating that combines radiation, reflection, and barrier mechanisms, the problem of insufficient thermal insulation performance of storage tank coatings has been solved, achieving high-efficiency thermal insulation, corrosion resistance, and environmental friendliness. It is suitable for cooling petrochemical storage tanks and environmentally friendly construction.
Patent Information
- Application Number
- CN202310813172.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-05
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2043-07-05
AI Technical Summary
Existing tank coatings suffer from insufficient heat insulation, poor corrosion resistance, low solar reflectivity, and poor environmental performance. Traditional solvent-based coatings pollute the environment and are complex to apply.
A water-based thermal insulation coating was prepared by using hollow glass microspheres, titanium dioxide, and modified carbon nanotubes, combining radiation, reflection, and barrier mechanisms, controlling particle size and addition amount, and using a water-based dispersion system with the addition of specific additives to improve the coating's thermal insulation, adhesion, and corrosion resistance.
It achieves high-efficiency heat insulation, acid and alkali resistance, and excellent corrosion resistance of water-based heat insulation coatings, reducing storage tank temperature, reducing oil evaporation, being environmentally friendly and pollution-free, and easy to apply.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coating preparation, and in particular to a water-based heat-insulating coating for petrochemical storage tanks and a preparation method thereof. Background Art
[0002] Storage tanks are sensitive to temperature. Under the sunlight in summer, the outer surface of the finished oil storage tank can reach a high temperature of 60-80℃, which will cause the temperature inside the tank to rise and accelerate the volatilization of the oil. The oil in the tank diffuses from the valve port of the tank to the surrounding environment, which not only causes the loss of oil, but also pollutes the environment and threatens the safety of the tank area. The traditional cooling method is to use spray precipitation to cool the outer wall of the storage tank, but this not only wastes water and electricity, but also easily accelerates the corrosion of the tank wall. Therefore, it is also necessary to develop and apply thermal insulation coatings to reduce the temperature inside the tank.
[0003] In addition to meeting the energy-saving and heat-insulating functions, environmental protection is an important requirement for the development of new materials today and in the future. The solvent-based coatings used in the construction of existing storage tanks contain a large amount of volatile organic compounds, which harm human health, pollute the environment, and create safety hazards. With the increasingly stringent environmental protection requirements, the application of water-based coatings will have a broader prospect.
[0004] The patent with publication number CN102127346 A introduces a thermal insulation coating and its preparation method, which uses ceramic hollow microspheres and aluminum silicate powder, but the corrosion resistance of the coating needs to be improved. CN103819989A discloses a water-based anticorrosive thermal insulation coating and its preparation method, which uses a single-coat, multifunctional coating prepared by metal-modified zinc phosphate, but the solar reflectance and acid and alkali resistance of the coating still need to be improved. CN109456668A "A weather-resistant reflective thermal insulation coating and its preparation method" improves the solar reflectance and weather resistance of the coating by adding silver-plated glass flakes. The patent CN107880675A "A high-performance hollow glass microsphere thermal insulation coating and its preparation method" introduces that the high-performance hollow glass microsphere thermal insulation coating can reduce the "indoor" ambient temperature after being applied to the exterior wall of a building. Summary of the invention
[0005] In order to solve the problems in the prior art, the present invention provides a water-based thermal insulation coating and a preparation method thereof. The coating provided by the present invention combines the three action mechanisms of radiation, reflection and barrier, and controls the particle size and addition amount of the filler, so that the coating has the characteristics of good thermal insulation, high adhesion and strong corrosion resistance.
[0006] In order to solve the above technical problems and realize the technical features of the present invention, the following technical solutions are provided: According to a first aspect of the present invention, the present invention provides a water-based thermal insulation coating, wherein the water-based thermal insulation coating comprises the following components in parts by weight: Hollow glass microspheres Ⅰ, 5-10 parts; Hollow glass microspheres II, 15-20 parts; Titanium dioxide, 10-20 parts; Emulsion, 30-45 parts; Modified carbon nanotubes, 0.1-2.5 parts; Auxiliary agent, 1-8 parts; Water, 10-25 parts.
[0007] Furthermore, the particle size of the hollow glass microspheres I is 60-120 μm, preferably 70-100 μm; the particle size of the hollow glass microspheres II is 1-50 μm, preferably 10-40 μm.
[0008] Furthermore, the titanium dioxide is rutile type, and has an average particle size of 0.3-20 μm.
[0009] Furthermore, the emulsion is one or more of styrene-acrylic emulsion, pure acrylic emulsion, polyurethane emulsion or fluorocarbon emulsion; preferably, the emulsion is two or more of the above emulsions.
[0010] Furthermore, the water-based paint also includes a curing agent, and the weight of the curing agent is 1 / 10-1 / 8 of the total amount of the paint. Furthermore, the required curing agent is a commercially available water-based curing agent.
[0011] Furthermore, the modified carbon nanotubes are carbon nanotubes modified by a Triton surfactant.
[0012] Further, the additives include dispersants, defoamers, neutralizers, multifunctional additives and thickeners. Preferably, each additive includes one type or two or more different types. The additives are all selected from conventional additives in the art. Preferably, the dispersant includes dispersant 1 and dispersant 2. Wherein, the acid value of dispersant 1 is 8 mg KOH / g or more (for example, BYK-190), and the acid value of dispersant 2 is less than 7 mg KOH / g (for example, BYK-2012). Preferably, the difference in acid value between dispersant 1 and dispersant 2 is 2 mgKOH / g or more, and the mass ratio of dispersant 1 to dispersant 2 is 7-10:1. Preferably, the thickener includes thickener 1 and thickener 2. Wherein, the viscosity (25°C) of thickener 1 is less than 16000 mPa.s (for example, Hemmings 420), and the viscosity of thickener 2 is greater than 20000 mPa.s (for example, Wanhua Chemical U605). Preferably, the viscosity difference between thickener 1 and thickener 2 is 5000 mPa.s or more, and the mass ratio of thickener 1 to thickener 2 is about 1.5-5.5:1. Among the auxiliary agents, the mass ratio of dispersant to thickener is generally 3-5:1. The multifunctional auxiliary agent has the functions of wetting, anti-settling, leveling and anti-sagging.
[0013] Furthermore, the modified carbon nanotubes can be prepared by conventional methods in the art. In the present invention, the following preparation method is recommended. The preparation method of the modified carbon nanotubes comprises the following steps: (1) Adding carbon nanotubes into a ball mill for ball milling; (2) dispersing the carbon nanotubes obtained by ball milling in step (1) in an aqueous solution containing triton to obtain a carbon nanotube suspension; (3) ultrasonically dispersing the carbon nanotube suspension obtained in step (2); (4) The suspension obtained in step (3) is separated, washed and dried to obtain the Triton-modified carbon nanotube powder.
[0014] Furthermore, in step (1), the ball milling time can generally be 20-40 min.
[0015] Furthermore, the mass fraction of the aqueous solution containing Triton in step (2) is generally 1-3 wt %; and the concentration of the suspension obtained in step (2) is generally 0.3-0.5 g / L.
[0016] Furthermore, in step (3), the dispersion time can generally be 20-40 min.
[0017] According to the second aspect of the present invention, the present invention also provides a method for preparing the above-mentioned water-based thermal insulation coating.
[0018] The preparation method of the water-based thermal insulation coating comprises the following steps: (1) Add the designed amount of dispersant, defoamer and neutralizer to the water in sequence while stirring, stir for a while, then add the designed amount of titanium dioxide and disperse evenly; (2) Grinding the material obtained in step (1) to obtain titanium dioxide slurry; (3) Add a portion of the designed amount of neutralizer to the titanium dioxide slurry, add the emulsion, then add the defoamer and the multifunctional additive, and stir for a while; slowly add the designed amount of hollow glass microspheres I under stirring, and then slowly add the designed amount of hollow glass microspheres II, and continue stirring; (4) adding water to prepare a modified carbon nanotube slurry, fully dispersing it, and obtaining a uniformly dispersed surface-modified carbon nanotube dispersion; adding the modified carbon nanotube dispersion to the material in step (3), and continuing to stir for a period of time; (5) Then continue to add the remaining dispersant, multifunctional additive, and thickener, and stir evenly to obtain the water-based thermal insulation coating.
[0019] Furthermore, in step (1), the stirring time is generally 20-40 min and the stirring speed is generally 1000-1500 r / min.
[0020] Furthermore, in step (2), the material obtained in step (1) is generally ground to a fineness of less than 60 μm.
[0021] Furthermore, in step (3), the stirring time is 10-30 min before adding the hollow microspheres, and the stirring time is continued for 10-20 min after adding the hollow microspheres. The stirring rate is generally 300-600 r / min.
[0022] Furthermore, in step (4), the concentration of the modified carbon nanotube slurry is 0.5-8 g / L. Preferably, the dispersion is carried out by ultrasonic dispersion, and the ultrasonic dispersion time is 0.5-2 h. The stirring time is 5-20 min. The stirring rate is generally 400-700 r / min.
[0023] Furthermore, the emulsion in step (3) is one or more of styrene-acrylic emulsion, pure acrylic emulsion, polyurethane emulsion or fluorocarbon emulsion; preferably, the emulsion is a two-component one. The required curing agent is a commercially available water-based curing agent.
[0024] Furthermore, the dispersant added in step (1) is dispersant 1, and the dispersant added in step (5) is dispersant 2. The addition ratio of dispersant 1 to dispersant 2 is about 7-10:1.
[0025] Furthermore, the thickener added in step (5) includes thickener 1 and thickener 2, and the addition ratio of thickener 1 to thickener 2 is about 1.5-5.5:1.
[0026] Furthermore, the particle size of the hollow glass microspheres I is 60-120 μm, preferably 70-100 μm; the particle size of the hollow glass microspheres II is 1-50 μm, preferably 10-40 μm.
[0027] Furthermore, the modified carbon nanotubes are carbon nanotubes that have been surface-modified with Triton.
[0028] Furthermore, the water is deionized water.
[0029] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention uses two hollow microspheres I and II of different particle sizes for combined use, and controls the content of small-sized microspheres to be greater than that of large-sized microspheres. The addition of a larger amount of small-sized hollow microspheres can fully and effectively fill the gaps between large-sized hollow microspheres, making the accumulation of microspheres more compact, which is conducive to improving the reflectivity. The reduced gap between the hollow microspheres and the resin can convert heat conduction into heat convection, thereby increasing the thermal insulation effect of the coating. At the same time, the two hollow microspheres of different sizes can be completely coated by the resin and evenly dispersed in the resin, thereby improving the thermal insulation effect of the coating.
[0030] 2. The present invention adds different additives in appropriate proportions, especially the use of two specific proportions of dispersants and thickeners, so that hollow microspheres of different particle sizes, modified carbon nanotubes and titanium dioxide are fully and evenly dispersed in the resin, with good film-forming and fluidity, and effectively improves the heat insulation, acid and alkali resistance and water resistance of the coating.
[0031] 3. In the water-based anti-corrosion and thermal insulation coating of the present invention, the carbon nanotubes modified with Qulaton can be better dispersed in the solution to provide good anti-corrosion and radiation properties, the hollow microspheres can provide better thermal insulation properties, and the titanium dioxide can provide good reflective properties. The three fillers act synergistically with each other to form a radiation + barrier + reflection thermal insulation effect, and work together to improve the thermal insulation properties of the water-based thermal insulation coating of the present invention.
[0032] 4. The water-based thermal insulation coating of the present invention is a single-coat, multifunctional coating with excellent anti-corrosion and thermal insulation properties, which is conducive to the promotion and utilization of the water-based thermal insulation coating products of the present invention. At the same time, the preparation and construction process of the coating products of the present invention are simple and easy to implement, which solves the problems of poor interlayer matching of multi-coat systems, long construction period, heavy odor of traditional oil-based paints, high pollution, etc., while ensuring various anti-corrosion and thermal insulation indicators.
[0033] 5. The water-based thermal insulation coating of the present invention adopts a water dispersion system, using water as a solvent to disperse the resin and filler system in water. When the coating film is cured, it mainly evaporates in the form of water, without polluting the atmosphere. Implementation
[0034] In order to make the technical problems to be solved, technical solutions and advantages of the present invention more clear, they are described in detail below in conjunction with specific embodiments.
[0035] The above scheme is further described below in conjunction with specific examples. It should be understood that these examples are used to illustrate the present invention and are not limited to the scope of the present invention. The implementation conditions adopted in the examples can be further adjusted according to the conditions of the specific manufacturer, and the unspecified implementation conditions are usually the conditions in conventional experiments.
[0036] The materials and reagents used in the following examples can all be obtained from commercial sources. Dispersant 1 is BYK-190, dispersant 2 is BYK-2012, defoamer is BYK-011, neutralizer is dimethylethanolamine, multifunctional additives include dipropylene glycol butyl ether and dipropylene glycol methyl ether, thickener 1 is Hemmings 420, and thickener 2 is Wanhua Chemical U605.
[0037] The present invention provides a water-based thermal insulation coating for a petrochemical storage tank and a preparation method thereof. The specific dosage of the materials and the experimental process are shown in the following examples. Example 1
[0038] Hollow glass microspheres Ⅰ, 5 parts; Hollow glass microspheres II, 15 parts; Titanium dioxide, 15 parts; Fluorocarbon emulsion, 40 parts; modified carbon nanotubes, 1 part; Auxiliary agent, 5 parts; Water, 19 parts; The auxiliary agents are commercially available dispersants 1 and 2, defoamers, neutralizers, multifunctional auxiliary agents, thickeners 1 and thickeners 2 in the art.
[0039] The preparation method of the modified carbon nanotubes is as follows: (1) Add a certain amount of carbon nanotubes into a ball mill and mill for 30 min; (2) adding a 2 wt % aqueous solution of Triton to dilute to 0.4 g / L to obtain a carbon nanotube suspension; (3) Place the suspension in an ultrasonic grinder and disperse for 30 min; (4) The suspension is filtered through a filter membrane, and after washing and drying, the carbon nanotube powder modified by Triton is obtained.
[0040] The preparation method of the above-mentioned water-based thermal insulation coating is: (1) Add the designed amount of dispersant 1, defoamer and neutralizer to water in sequence at a stirring speed of 1200 r / min, stir for 30 min, then add the designed amount of titanium dioxide and disperse evenly; (2) Grinding again until the fineness is less than 60 μm to obtain color paste; (3) After adding the neutralizer to the color paste, add the fluorocarbon emulsion, then add the defoamer and the multifunctional additive, stir for 20 minutes, then slowly add the designed amount of hollow glass microspheres I at a stirring speed of 500 r / min, and then slowly add the designed amount of hollow glass microspheres II and stir; (4) Add water to prepare 2 g / L modified carbon nanotube slurry, and after ultrasonic dispersion for 1 h, obtain a uniformly dispersed modified carbon nanotube dispersion, add the modified carbon nanotube dispersion to the color paste of step (3), and stir for 15 min at a stirring speed of 500 r / min for 10 min; (5) Finally, add dispersant 2, multifunctional additive, thickener 1 and thickener 2, and stir evenly to obtain a water-based thermal insulation coating. Example 2
[0041] A water-based heat-insulating coating, composed of the following parts by weight: Hollow glass microspheres Ⅰ, 10 parts; Hollow glass microspheres II, 15 parts; Titanium dioxide, 20 parts; Polyurethane emulsion, 35 parts; Auxiliary agent, 5 parts; modified carbon nanotubes, 0.5 parts; Water, 14.5 parts; The auxiliary agents are commercially available dispersants 1 and 2, defoamers, neutralizers, multifunctional auxiliary agents, thickeners 1 and thickeners 2 in the art.
[0042] The preparation method of the modified carbon nanotubes is the same as that in Example 1.
[0043] The preparation method of the above-mentioned water-based thermal insulation coating is: (1) Add the designed amount of dispersant 1, defoamer and neutralizer to water in sequence at a stirring speed of 1400 r / min, stir for 20 min, then add the designed amount of titanium dioxide and disperse evenly; (2) Grinding again until the fineness is less than 60 μm to obtain color paste; (3) After adding the neutralizer to the color paste, add the polyurethane emulsion, then add the defoamer and the multifunctional additive, stir for 15 minutes, then slowly add the designed amount of hollow glass microspheres I at a stirring speed of 400 r / min, and then slowly add the designed amount of hollow glass microspheres II and stir; (4) Add water to prepare 3 g / L modified carbon nanotube slurry, and after ultrasonic dispersion for 1 h, obtain a uniformly dispersed modified carbon nanotube dispersion, add the surface-modified carbon nanotube dispersion to the color paste of step (3), and stir for 15 min at a stirring speed of 500 r / min; (5) Finally, add dispersant 2, multifunctional additive, thickener 1 and thickener 2, and stir evenly to obtain a water-based thermal insulation coating. Example 3
[0044] A water-based heat-insulating coating, composed of the following parts by weight: Hollow glass microspheres Ⅰ, 8 parts; Hollow glass microspheres II, 18 parts; Titanium dioxide, 12 parts; Polyurethane emulsion, 38 parts; Auxiliary agent, 8 parts; modified carbon nanotubes, 0.2 parts; Water, 15.8 parts.
[0045] The preparation method of the modified carbon nanotubes is the same as that in Example 1.
[0046] The preparation method of the above-mentioned water-based thermal insulation coating is the same as that of Example 2.
[0047] Comparative Example 1 This comparative example does not contain hollow glass microspheres I, and all hollow microspheres are hollow microspheres II. The rest is the same as in Example 1.
[0048] Comparative Example 2 This comparative example does not contain hollow glass microspheres II, all hollow microspheres are hollow microspheres I, and the rest is the same as Example 1.
[0049] Comparative Example 3 In this comparative example, only 5 parts of titanium dioxide were added, and the rest was the same as in Example 1.
[0050] Comparative Example 4 This comparative example is a common carbon nanotube dispersion, and the rest is the same as Example 1.
[0051] Comparative Example 5 In this comparative example, the hollow glass microspheres I are 15 parts, the hollow glass microspheres II are 5 parts, and the rest are the same as in Example 1.
[0052] Comparative Example 6 In this comparative example, the content of the modified carbon nanotube slurry is 4 parts, and the rest is the same as in Example 1.
[0053] Comparative Example 7 In this comparative example, only dispersant 1 is added as the dispersant in the auxiliary agent, and the rest is the same as in Example 1.
[0054] Comparative Example 8 In this comparative example, only thickener 1 is added as the thickener in the auxiliary agent, and the rest is the same as in Example 1.
[0055] Comparative Example 9 The carbon nanotubes in this comparative example are commercially available amino-modified carbon nanotubes, and the rest are the same as those in Example 1.
[0056] The compositions of the coatings obtained in Examples 1-3 and Comparative Examples 1-9 are listed in Table 1.
[0057] Table 1 Coating composition (unit, parts by weight) Hollow glass microspheres Ⅰ Hollow glass microspheres Ⅱ Titanium dioxide Fluorocarbon / polyurethane emulsion Additives Modified carbon nanotubes water Example 1 5 15 15 40 5 1 19 Example 2 10 15 20 35 5 0.5 14.5 Example 3 8 18 12 38 8 0.2 15.8 Comparative Example 1 0 20 15 40 5 1 19 Comparative Example 2 20 0 15 40 5 1 19 Comparative Example 3 5 15 5 40 5 1 29 Comparative Example 4 5 15 15 40 5 1 (ordinary carbon nanotubes) 20 Comparative Example 5 15 5 15 40 5 1 19 Comparative Example 6 5 15 15 40 5 4 16 Comparative Example 7 5 15 15 40 5 (containing dispersant 1 only) 1 19 Comparative Example 8 5 15 15 40 5 (Contains only thickener 1) 1 19 Comparative Example 9 5 15 15 40 5 1 (Commercially available amino-modified carbon nanotubes) 19 The coatings prepared in the above Examples 1-3 and Comparative Examples 1-9 were tested for reflectivity (test method refer to JG / T235), hemispherical emissivity (test method refer to GB / T 2680) and chemical resistance (test method refer to GB / T9274), and the test results are shown in Table 2.
[0058] Table 2 Comparison of test results Serial number Reflectivity / % Hemispherical emissivity / % <![CDATA[Acid resistant (5% H 2 SO 4 )]]> Alkali resistance (5% NaOH) Salt water resistance (3% NaCl) Example 1 90.3 87 No change in paint film after 720h immersion No change in paint film after 192h immersion No change in paint film after 192h immersion Example 2 89.2 89 No change in paint film after 720h immersion No change in paint film after 192h immersion No change in paint film after 192h immersion Example 3 89.6 85 No change in paint film after 720h immersion No change in paint film after 192h immersion No change in paint film after 192h immersion Comparative Example 1 83.0 85 After immersion for 720 hours, the paint film loses gloss and bubbles appear. After 192 hours of immersion, the paint film loses gloss and bubbles appear. No change in paint film after 192h immersion Comparative Example 2 82.0 85 After immersion for 720 hours, the paint film loses gloss and bubbles appear. After 192 hours of immersion, the paint film loses gloss and bubbles appear. After 192 hours of immersion, the paint film loses gloss and bubbles appear. Comparative Example 3 78.0 80 After immersion for 672 hours, the paint film loses gloss and bubbles appear. After 144 hours of immersion, the paint film loses gloss and bubbles appear. After 144 hours of immersion, the paint film loses gloss and bubbles appear. Comparative Example 4 87.0 74 After immersion for 660 hours, the paint film loses gloss and bubbles appear. After immersion for 120 hours, the paint film loses gloss and bubbles appear. After 144 hours of immersion, the paint film loses gloss and bubbles appear. Comparative Example 5 86.0 84 After immersion for 720 hours, the paint film loses gloss and bubbles appear. After 192 hours of immersion, the paint film loses gloss and bubbles appear. After 192 hours of immersion, the paint film loses gloss and bubbles appear. Comparative Example 6 88.6 84 After immersion for 720 hours, the paint film loses gloss and bubbles appear. After 192 hours of immersion, the paint film loses gloss and bubbles appear. After 192 hours of immersion, the paint film loses gloss and bubbles appear. Comparative Example 7 87.4 82 After immersion for 672 hours, the paint film loses gloss and bubbles appear. After 168 hours of immersion, the paint film loses gloss and bubbles appear. After 168 hours of immersion, the paint film loses gloss and bubbles appear. Comparative Example 8 88.1 83 After immersion for 696 hours, the paint film loses gloss and bubbles appear. After 168 hours of immersion, the paint film loses gloss and bubbles appear. After 168 hours of immersion, the paint film loses gloss and bubbles appear. Comparative Example 9 87.2 75 After immersion for 660 hours, the paint film loses gloss and bubbles appear. After immersion for 120 hours, the paint film loses gloss and bubbles appear. After 144 hours of immersion, the paint film loses gloss and bubbles appear. It can be seen from the example results in Table 2 that the water-based reflective thermal insulation coating prepared by the present invention has good thermal insulation performance and excellent acid resistance and alkali resistance. Comparing the embodiment with comparative examples 1 and 2, it is found that the reflectivity of the coating with only hollow glass microspheres of a single size is reduced, and the hemispherical emissivity and acid and alkali resistance do not change much; from comparative example 3, it can be seen that after the titanium dioxide content is reduced, the reflectivity, hemispherical emissivity, acid and alkali resistance and water resistance of the coating are all reduced; from comparative example 4, it can be seen that after the modified carbon nanotubes are changed to ordinary carbon nanotubes, the hemispherical emissivity of the coating is significantly reduced, and the acid and alkali resistance and water resistance are also reduced; from comparative example 5, it can be seen that when the content of the added large-sized hollow glass microspheres I is much greater than that of the small-sized hollow glass microspheres II, the reflectivity of the coating decreases, but it has little effect on the hemispherical emissivity, acid and alkali resistance and water resistance of the coating; from comparative example 6, it can be seen that when the content of the added modified carbon nanotubes is increased to 4 parts, the hemispherical emissivity of the coating is not the maximum, indicating that if the content of the added carbon nanotubes is too large, the hemispherical incidence of the coating will not increase accordingly, but will decrease instead. It can be seen from Comparative Example 7 that when only a single dispersant 1 is used, the reflectivity, hemispherical emissivity, acid and alkali resistance and water resistance of the coating are all reduced; it can be seen from Comparative Example 8 that when only a single thickener 1 is used, the reflectivity, hemispherical emissivity, acid and alkali resistance and water resistance of the coating are all reduced compared with the embodiment; it can be seen from Comparative Example 9 that after the Triton modified carbon nanotubes are replaced with ordinary amino modified carbon nanotubes, the hemispherical emissivity of the coating is significantly reduced, and the acid and alkali resistance and water resistance are also reduced.
[0059] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. For ordinary technicians in this technical field, several improvements can be made without departing from the principles of the present invention. These improvements should also be regarded as within the scope of protection of the present invention.
Claims
1. A water-based thermal insulation coating, characterized in that: The composition comprises the following components in parts by weight: Hollow glass microspheres Ⅰ, 5-10 parts; Hollow glass microspheres II, 15-20 parts; Titanium dioxide, 10-20 parts; Emulsion, 30-45 parts; Modified carbon nanotubes, 0.1-2.5 parts; Auxiliary agent, 1-8 parts; Water, 10-25 parts; Wherein, the particle size of the hollow glass microspheres I is 60-120 μm, preferably 70-100 μm; the particle size of the hollow glass microspheres II is 1-50 μm, preferably 10-40 μm.
2. The water-based thermal insulation coating according to claim 1, characterized in that: The titanium dioxide is rutile type and has an average particle size of 0.3-20 μm.
3. The water-based thermal insulation coating according to claim 1, characterized in that: The emulsion is one or more of styrene acrylic emulsion, pure acrylic emulsion, polyurethane emulsion or fluorocarbon emulsion; preferably, the emulsion is two or more of the above emulsions.
4. The water-based thermal insulation coating according to claim 1, characterized in that: The modified carbon nanotubes are carbon nanotubes modified by a Triton surfactant.
5. The water-based thermal insulation coating according to claim 1, characterized in that: The auxiliary agent includes one or more of a dispersant, a defoamer, a neutralizer, a multifunctional auxiliary agent and a thickener; the mass ratio of the dispersant to the thickener is 3-5:
1.
6. The water-based thermal insulation coating according to claim 5, characterized in that: The dispersants include dispersant 1 and dispersant 2. The acid value of dispersant 1 is greater than 8 mg KOH / g, and the acid value of dispersant 2 is less than 7 mg KOH / g. The mass ratio of dispersant 1 to dispersant 2 is 7-10:
1.
7. The water-based thermal insulation coating according to claim 5, characterized in that: The thickener includes thickener 1 and thickener 2; the viscosity (25°C) of thickener 1 is less than 16000 mPa.s, and the viscosity of thickener 2 is greater than 20000 mPa.s; the mass ratio of thickener 1 to thickener 2 is about 1.5-5.5:
1.
8. The water-based thermal insulation coating according to claim 4, characterized in that: The preparation method of the modified carbon nanotubes comprises the following steps: (1) Adding carbon nanotubes into a ball mill for ball milling; (2) dispersing the carbon nanotubes obtained by ball milling in step (1) in an aqueous solution containing triton to obtain a carbon nanotube suspension; (3) ultrasonically dispersing the carbon nanotube suspension obtained in step (2); (4) The suspension obtained in step (3) is separated, washed and dried to obtain the Triton-modified carbon nanotube powder.
9. The water-based thermal insulation coating according to claim 8, characterized in that: The mass fraction of the aqueous solution containing Triton in step (2) is 1-3wt%; the concentration of the suspension obtained in step (2) is 0.3-0.5 g / L.
10. The water-based thermal insulation coating according to any one of claims 1 to 9, characterized in that: The water-based paint also includes a curing agent, and the weight of the curing agent is 1 / 10-1 / 8 of the total amount of the paint.
11. The method for preparing the water-based thermal insulation coating according to any one of claims 1 to 10, characterized in that: The following steps are involved: (1) Add the designed amount of dispersant, defoamer and neutralizer to the water in sequence while stirring, stir for a while, then add the designed amount of titanium dioxide and disperse evenly; (2) Grinding the material obtained in step (1) to obtain titanium dioxide slurry; (3) Add a portion of the designed amount of neutralizer to the titanium dioxide slurry, add the emulsion, then add the defoamer and multifunctional additive, and stir for a while; Slowly add the designed amount of hollow glass microspheres I under stirring, then slowly add the designed amount of hollow glass microspheres II, and continue stirring; (4) adding water to prepare a modified carbon nanotube slurry, fully dispersing it, and obtaining a uniformly dispersed surface-modified carbon nanotube dispersion; adding the modified carbon nanotube dispersion to the material in step (3), and continuing to stir for a period of time; (5) Then continue to add the remaining dispersant, multifunctional additive, and thickener, and stir evenly to obtain the water-based thermal insulation coating.
12. The preparation method according to claim 11, characterized in that: In step (2), the material obtained in step (1) is ground to a fineness of less than 60 μm.
13. The preparation method according to claim 11, characterized in that: The stirring time in step (3) is 10-30 minutes before adding the hollow microspheres, and the stirring time is continued for 10-20 minutes after adding the hollow microspheres.
14. The preparation method according to claim 11, characterized in that: The concentration of the modified carbon nanotube slurry in step (4) is 0.5-8 g / L.
15. The preparation method according to claim 11, characterized in that: The dispersion in step (4) is carried out by ultrasonic dispersion, and the time of the ultrasonic dispersion is 0.5-2 h.
16. The preparation method according to claim 11, characterized in that: The dispersant added in step (1) is dispersant 1, and the dispersant added in step (5) is dispersant 2; the mass ratio of dispersant 1 to dispersant 2 is 7-10:
1.
17. The preparation method according to claim 11 or 16, characterized in that: The thickener added in step (5) includes thickener 1 and thickener 2, and the mass ratio of thickener 1 to thickener 2 is 1.5-5.5:1.
Citation Information
Patent Citations
Thermal insulation coating and preparation method thereof
CN102127346A
Aqueous anticorrosive heat-insulation paint and preparation method
CN103819989A
High-performance hollow glass bead thermal insulation paint and preparation method thereof
CN107880675A
Weather-resistant reflective heat insulation coating and preparation method thereof
CN109456668A
Multi-functional building exterior wall environment-friendly nano-coating and preparation method thereof
CN105504914A